Climate change and pollinator dynamics: integrating social media insights and ecological data for conservation strategies - Pooja Hadimane; Ashoka Kukkuvada; Gangamma Hediyalad; Govardhan Hegade Kota; Rajeswari Kisan; Shivanand Patil; Arjun Myala; Basavaraja Anekonda Subhash (IAES International Journal of Artificial Intelligence (IJ-AI), 2026)
Pollination is an essential ecosystem service intricately linked to biodiversity, ecosystem health, and agricultural systems. The need to understand the effect of climate change on pollination processes has never been greater, given that a significant portion of global crop production is dependent on biotic pollination. This survey paper examines the multifaceted challenges that climate change poses to pollination dynamics across various ecosystems. By synthesizing existing literature to highlight how alterations in temperature and precipitation patterns have led to a phenological mismatch between pollinators and plants, potentially disrupting established trophic relationships and ecosystem functions. Our review reveals that insect-pollinated plants, particularly those that bloom early in the season, exhibit a heightened sensitivity to climate-induced phenological shifts. Moreover, exploring how the altered life cycles of pollinators, struggling to synchronize with the new flowering schedules, may precipitate declines in pollination services. Our findings underscore the critical need for conservation strategies that address climate adaptation for pollinators, focusing on enhancing landscape connectivity and heterogeneity. By bridging diverse studies ranging from the application of social media data in ecological research to advanced predictive models for pollination services, the main aim is to foster a deeper understanding of the consequences of climate change on pollination.